PHYSICS, TECHNOLOGIES AND INNOVATION (PTI-2019): Proceedings of the VI International Young Researchers’ Conference 2019
DOI: 10.1063/1.5134387
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of food processing biotechnology in developing countries

Abstract: Biotechnology is an applied science which represents a blending of the principles and practice of biochemistry, genetics and microbiology. The recent breakthroughs in molecular biology have transformed biotechnology into a precision science. These developments have brought in further refinements to areas like protein chemistry, nucleic acid biochemistry, fermentation and immunology, which unfortunately are not common to developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…The defatting process would significantly improve ( p< 0.05)the mineral content of the flour samples. Na (ranging from 223.92–246.99 mg/100g) and K (ranging from 211.04–178.45 mg/100g) appear to be the most abundant, while P (ranging from 1.78–1.92 mg/100g) and Mn (ranging from 1.14 to 1.64 mg / 100g) appear least abundant in the melon seed flour of this study, corroborating the data reported elsewhere [ 3 ]. The function of P is for bone mineralization and energy transfer, Ca for bone development and growth, Mg for cardiac and smooth muscle contractibility, K for contraction of smooth, skeletal, and cardiac muscle, as well as Na for nerve transmission and regulation of fluid balance [ 25 ].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The defatting process would significantly improve ( p< 0.05)the mineral content of the flour samples. Na (ranging from 223.92–246.99 mg/100g) and K (ranging from 211.04–178.45 mg/100g) appear to be the most abundant, while P (ranging from 1.78–1.92 mg/100g) and Mn (ranging from 1.14 to 1.64 mg / 100g) appear least abundant in the melon seed flour of this study, corroborating the data reported elsewhere [ 3 ]. The function of P is for bone mineralization and energy transfer, Ca for bone development and growth, Mg for cardiac and smooth muscle contractibility, K for contraction of smooth, skeletal, and cardiac muscle, as well as Na for nerve transmission and regulation of fluid balance [ 25 ].…”
Section: Resultssupporting
confidence: 92%
“…[ 28 ]. Overall, the WAC data here compete with full-fat /defatted seed flours reported elsewhere [ 3 , 21 , 23 , 28 ].…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations